Penerapan Algoritme Prim dan Floyd-Warshall sebagai Algoritme Routing pada Arsitektur Software Defined Network - Ariefanda Junediansyah; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Software Defined Network is a concept of computer network approach where the control system of data flow is separated from other devices. The control system or controller is responsible for defining the network, managing availability issues, traffic data rates, routing and forwarding and others. Routing is the process of determining the route or path taken by packets as they flow from sender to receiver. In finding the shortest route, a routing algorithm is needed. In this study, the routing algorithms used are Floyd-Warshall and Prim. In general, Prim's algorithm is often used to solve Minimum Spanning Tree problems on graphs to minimize tree spans or reduce the number of branches. In this study Prim's algorithm is used to find the shortest route, then compared with the Floyd-Warshall algorithm. Both algorithms are implemented in a hybrid topology using a mininet emulator and a Ryu controller. Determination of the path required path cost. Cost determination is based on the results of the calculation for the reference bandwidth of 1000 Mbps and link bandwidth using three types of capacity sizes, namely 1000 Mbps, 100 Mbps and 10 Mbps. Then tested with the parameters of convergence time and recovery time as many as 30 trials on each algorithm. From the test results, it is found that the application of Prim's algorithm finds the shortest route faster and finds a new route faster when a link failure occurs.